2019
DOI: 10.1038/s41598-019-48196-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PFKFB3 alleviates cerebral ischemia-reperfusion injury in mice

Abstract: The glycolytic rate in neurons is low in order to allow glucose to be metabolized through the pentose-phosphate pathway (PPP), which regenerates NADPH to preserve the glutathione redox status and survival. This is controlled by 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 (PFKFB3), the pro-glycolytic enzyme that forms fructose-2,6-bisphosphate, a powerful allosteric activator of 6-phosphofructo-1-kinase. In neurons, PFKFB3 protein is physiologically inactive due to its proteasomal degradation. Howeve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…In their efforts to design potent and selective inhibitors of metabolic kinase PFKFB3, Boyd et al, reported a series of inhibitors with high selectivity over the related PFKFB3 isoform. Among these, AZ67 was the focus of our study, as it has a high selectivity for PFKFB3 compared to other isoforms, it decreases F-2,6-P 2 levels, and it inhibits PFKFB3 kinase activity—showing good activity in the cell assays, albeit with no apparent effects on lactate production [ 33 , 36 ]. This latter effect, later also confirmed in astrocytes [ 36 ], was an interesting point when confirming angiogenesis reduction upon PFKFB3 blockage with no impact on the glycolysis pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their efforts to design potent and selective inhibitors of metabolic kinase PFKFB3, Boyd et al, reported a series of inhibitors with high selectivity over the related PFKFB3 isoform. Among these, AZ67 was the focus of our study, as it has a high selectivity for PFKFB3 compared to other isoforms, it decreases F-2,6-P 2 levels, and it inhibits PFKFB3 kinase activity—showing good activity in the cell assays, albeit with no apparent effects on lactate production [ 33 , 36 ]. This latter effect, later also confirmed in astrocytes [ 36 ], was an interesting point when confirming angiogenesis reduction upon PFKFB3 blockage with no impact on the glycolysis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, AZ67 was the focus of our study, as it has a high selectivity for PFKFB3 compared to other isoforms, it decreases F-2,6-P 2 levels, and it inhibits PFKFB3 kinase activity—showing good activity in the cell assays, albeit with no apparent effects on lactate production [ 33 , 36 ]. This latter effect, later also confirmed in astrocytes [ 36 ], was an interesting point when confirming angiogenesis reduction upon PFKFB3 blockage with no impact on the glycolysis pathway. This was important as other groups have reported that PFKFB3-driven glycolysis directly modulates vessel sprouting [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these pathways of relevance are "Sirtuin Signaling Pathway", "fibroblast growth factor (FGF) Signaling" and "Interferon (IFN) Signaling". The gene 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) and FGF Receptor 3 (FGFR3) respectively belong to the first and second pathway, and are known to positively regulate cell generation and proliferation 48,49 . Whereas the gene interferon induced transmembrane protein 3 (1-8U) (IFITM3) belongs to the last signaling pathway and it is involved in the innate inflammatory response and known to suppress cell proliferation 50 .…”
Section: Epa Prevents the Detrimental Effect Of Cortisol Via Modulatimentioning
confidence: 99%
“…We undertook this by inhibiting PFKFB3 activity using the highly selective, rationally designed 34 compound AZ67. Incubation of Cln7 Δ ex2 neurons with AZ67 at a concentration that inhibits PFKFB3 activity without compromising survival 35 , prevented the increase in F-2,6-P2 ( Fig. 4a ) and glycolysis ( Fig.…”
mentioning
confidence: 93%